TRUST Study: Participation in Randomized Controlled Trials and Subsequent Adherence to Visiting Medical Institutions and Taking Medications in Patients with Cardiovascular Diseases. Part I. Motives for the Patients' Participation in Clinical Trials - S. Yu. Martsevich; N. O. Vasyukova; N. P. Kutishenko; Yu. V. Lukina; O. I. Zvonareva (Столичная издательская компания, 2019)
Aim. To describe the design of TRUST study (Influence of Participation in Randomized Controlled Trials on adheRence to Medicines' Intake and regUlar viSits to the docTor) and present the first part of this study to determine the motives of patient participation in clinical trials.Material and methods. The main group of TRUST study included patients of the outpatient registrar PROFILE, which were taking part in one or more international randomized clinical trials, conducted from 2011 to 2018. The standard registration card of PROFILE register was used to assess the clinical and demographic data of patients.In 2019 full-time/telephone contact with patients was established, during which, based on the original questionnaire, the motives of the participation in trials, their attitude towards randomized controlled trials (RCT), and their adherence to monitoring in medical institutions were determined. This publication presents the results of the first part of the study.Results. 102 patients were enrolled in the study, telephone /personal contact was established for 88 patients, the life status of 9 of them by 2019 was defined as "dead", 77 were interviewed, 2 - refused to answer. Over 80% of patients completed participation in RCTs more than one year ago. 71.6% of patients participated in more than one RCT. In 60% of cases, patients claimed that this was the proposal of the doctor of the scientific center. For 79% of patients, RCTs had the opportunity to access highly skilled medical care. Only 18% of patients indicated that they received the necessary qualified medical care before entering the study. In cases where patients answered dichotomous questions (such as "yes"/"no"), the overwhelming majority of patients (74%) claimed that it was the authority of the doctor of the scientific center and the fear of losing the possibility of further observation became the main reason for participating in RCTs.Conclusion. In the first part of the TRUST study, it was revealed that in Russia the main reason of participation in RCT is the recommendation of a doctor from a specialized scientific center.